A comparison of the dimensionality of the Hamilton Rating Scale for anxiety and the DSM-5 Anxious-Distress Specifier Interview. (February 2020) - Rodriguez-Seijas, Craig; Thompson, Justine S.; Diehl, Joseph M.; Zimmerman, Mark
Highlights: The factor structure of the Hamilton Rating Scale for Anxiety (HAM-A) is confounded by the assessment of symptoms of depression. The DSM-5 Anxious Distress Specifier has been proposed to measure anxiety among individuals with a major depressive episode, though there is scant empirical literature on the nature of anxious distress. The factor structures of the HAM-A and one assessment tool of anxious distress were assessed among psychiatric patients with and without a current major depressive disorder. Optimal HAM-A factor structure differed based upon diagnosis of a major depressive disorder, while the anxious distress specifier interview demonstrated similar factor structure in both groups. Abstract: The Hamilton Rating Scale for Anxiety (HAM-A) is one of the most widely used measures for assessing anxiety in research settings. However, it has been criticized for its inclusion of items that assess depressive symptoms. The DSM -5 Anxious Distress Specifier Interview (DADSI), developed as one assessment tool for measuring anxiety among depressed patients, demonstrates similar validity when compared with the HAM-A. However, its underlying factor structure has never been explored. The goal of the current study, therefore, was to compare the underlying factor structures of the HAM-A and the DADSI among clinically depressed ( n  = 576) and non-depressed ( n  = 146) patient samples. While two- and three-factor structures of the HAM-A fit similarly well among patients with a current major depressive episode, the three-factor structure—with anxiety and depressive symptoms forming separate factors—fit best among patients without a current major depressive episode. The DADSI was best represented by a single-factor model in both groups. The DADSI showed stronger associations with anxiety and somatic symptoms than with depressive symptoms of the HAM-A. These findings add to the characterization of the DADSI, and further highlight an important consideration for the use of HAM-A as a measure of anxiety in outcome studies.